The Use of the Internet and the Hospitality of Hotels In The Old Royal Road - Pozo, Hamilton (International Journal of Scientific Research and Management (IJSRM), 2023)
The research presents a diagnosis using the internet and hospitality in hotels of Old Royal Road path in the scope of Ouro Preto (Minas Gerais) to Paraty (Rio de Janeiro) as a competitive edge, and that affects the volume of Bookings for these hotels. A study of 17 hotels in seven (7) cities in the Old Royal Road was made. The survey found the relationship between hotels and their customers, forms of dissemination of projects and realization of reserves, as well as knowledge of managers regarding the implementation and expansion of Internet use. The research method is a multiple-case survey with semi-structured interviews. Observation of processes and document analysis were used for data collection adopted in the preparation of this work. Respondents were hotel managers and owners, case study object. The research also demonstrates the considerable growth of internet use in hotels surveyed, the features of websites, and especially the business opportunities to increase competitiveness. Using technology to research and compare prices, brands, forms of payment, and detailed information on the products and services without leaving home seduces the consumer. The hotel industry is also increasingly integrating with the virtual world process and getting hit with customers.